Theoretical investigation of the instability of hybrid halide perovskites - Zheng, Chao (My University, 2019)
It has been 10 years since the first hybrid halide perovskite photovoltaics was fabricated. Power conversion efficiency increases from the initial 3.8% to the current 25.2%. Fabrication method envolves from spin-coating to printable technology, and we deeply experience the drastic development of hybrid halide perovskite photovoltaics. Although hybrid halide photovoltaics render a variety of advantages over traditional photovoltaics, we still cannot find any practical application of these hybrid halide photovoltaics. There exist a few issues which hinder the commercialization of this type of solar cell. Among these issues, the long-term instability of hybrid halide perovskite is the main concern for the next development. This thesis expands on investigating the instability of hybrid halide perovskites from first principles. In Chapter 1, two computational methods employed in the thesis: density functional theory and Ab initio molecular dynamics are introduced. Theoretical investigations of the instability of CH3NH3PbI3 using density functional theory method are mainly conducted at 0 K. The finite temperature effect on this instability of CH3NH3PbI3 is usually neglected. In Chapter 2 of this thesis, we combined density functional calculations and additional thermodynamic data to explain the intrinsic instability of CH3NH3PbI3 under finite temperature conditions. We also analyzed the stability under humid conditions. It is shown that the aqueous solubilities of reactants play an important role in the products’ stabilities. The Born–Haber cycle of NaCl splits the enthalpy change into several components which will give a better understanding of the origin of the corresponding enthalpy change. In Chapter 3, with the extension of the Born–Haber cycle to the hybrid halide perovskites, the reaction enthalpies which govern the intrinsic instability of ionic compounds were analyzed. We proposed a criterion that helps to filter the hybrid halide perovskites with improved stability aimed for photovoltaics. Since the instability of CH3NH3PbI3 is intrinsic. The long-term instability can be settled by discovering alternative perovskite absorber. In Chapter 4, based on literature research, we propose a three-membered ring cation which has a suitable size to fit into the Pb-I framework, leading to optimal band gap for photovoltaics. Besides, the cation has a good ionization energy which will potentially render better stability. Whereas, a comprehensive study of this cyclic ring based perovskite indicates that the instability of the three-membered ring cation will make it impossible to synthesize this theoretical structure. Moisture degradation mechanisms of CH3NH3PbI3 are investigated intensively. More importantly, for practical photovoltaics, we have to imagine different situations the modules will encounter, e.g. after a couple of years, cracks appearing on the modules are inevitable, at this stage, understanding of the degradation mechanism of CH3NH3PbI3 according to liquid water becomes important. Chapter 6 elaborately describes a comprehensive degradation mechanism of CH3NH3PbI3 under liquid water. We investigate the energy barrier for the first dissolution event of CH3NH3PbI3 in water. Furthermore, thermodynamic analyses of CH3NH3PbI3 dissolution in water clearly explain the spontaneity of CH3NH3PbI3 degradation in water. Besides, different mechanisms of CH3NH3PbI3 and CsPbI3 dissolution in water are discussed.
Keywords: hybrid halide perovskites; density functional theory; molecular dynamics; metadynamics; thermodynamics